On Cyclic Generalized Weakly C-Contractions on Partial Metric Spaces - Erdal Karapınar; Vladimir Rakocević (Journal of Applied Mathematics)
We give new results of a cyclic generalized weakly C-contraction in partial metric space. The results of this paper extend, generalize, and improve some fixed point theorems in the literature.